(untitled) (e-Journal of Linguistics, 2023)
The feud between PS Glow and MS Glow became a conversation that caught the public’s attention. One of the parties is considered to have the same principal trademark, so the intention to imitate, plagiarize or follow the other party’s brand for business purposes creates unhealthy business conditions and deceives or misleads consumers. This study analyzes the trademark dispute between PS Glow and MS Glow. The data sources in this study are the Decisions of the Supreme Court of the Republic of Indonesia Number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Mdn and Number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Sby. This research uses methods and techniques which are divided into three stages, namely (1) the data collected by observation method assisted by note-taking technique; (2) Data analysis using qualitative methods. The data analysis technique used descriptive technique; and (3) Presentation of the data analysis results using informal and formal methods. The results show that PS Glow and MS Glow are other trademarks. It can be seen based on the analysis at the phonological level, namely the presence of sounds that can distinguish meaning, namely /p/ - /m/. Thus, it can be said that the decisions of judges are considered inaccurate.